A rare cause of severe Cushing's syndrome. (13th March 2020) - Zaman, Shamaila; Patel, Bijal; Glynne, Paul; Vanderpump, Mark; Alsafi, Ali; Khan, Sairah; Flora, Rashpal; Palazzo, Fausto; Wernig, Florian
Abstract : Summary: Ectopic adrenocorticotropic hormone (ACTH) production is an uncommon cause of Cushing's syndrome and, rarely, the source can be a phaeochromocytoma. A 55-year-old man presented following an episode of presumed gastroenteritis with vomiting and general malaise. Further episodes of diarrhoea, joint pains and palpitations followed. On examination, he was hypertensive with no clinical features to suggest hypercortisolaemia. He was subsequently found to have raised plasma normetanephrines of 3.98 nmol/L (NR <0.71) and metanephrines of 0.69 nmol/L (NR <0.36). An adrenal CT showed a 3.8 cm right adrenal nodule, which was not MIBG-avid but was clinically and biochemically consistent with a phaeochromocytoma. He was started on alpha blockade and referred for right adrenalectomy. Four weeks later, on the day of admission for adrenalectomy, profound hypokalaemia was noted (serum potassium 2.0 mmol/L) with non-specific ST-segment ECG changes. He was also diagnosed with new-onset diabetes mellitus (capillary blood glucose of 28 mmol/L). He reported to have gained weight and his skin had become darker over the course of the last 4 weeks. Given these findings, he underwent overnight dexamethasone suppression testing, which showed a non-suppressed serum cortisol of 1099 nmol/L. Baseline serum ACTH was 273 ng/L. A preliminary diagnosis of ectopic ACTH secretion from the known right-sided phaeochromocytoma was made and he was started on metyrapone and insulin. Surgery was postponed for 4 weeks. Following uncomplicated laparoscopic adrenalectomy, the patient recovered with full resolution of symptoms. Learning points: Phaeochromocytomas are a rare source of ectopic ACTH secretion. A high clinical index of suspicion is therefore required to make the diagnosis. Ectopic ACTH secretion from a phaeochromocytoma can rapidly progress to severe Cushing's syndrome, thus complicating tumour removal. Removal of the primary tumour often leads to full recovery. The limited literature suggests that the presence of ectopic Cushing's syndrome does not appear to have any long-term prognostic implications.